Microbiological quality of sushi sampled from selected food outlets in Kota Bharu, Kelantan - Sandrasekharan, Vanitaa (Universiti Sains Malaysia, 2015)
As a ready-to-eat food sushi is also prone to microbial contamination and it has been associated with food borne outbreaks. A study was conducted to evaluate the microbiological quality of 30 sushi which were randomly sampled from selected food outlets in Kota Bharu, Kelantan from November 2014 until February 2015. A total of 9 (30%) samples exceeded the proposed guidelines for total plate count and 8 (23.33%) samples for total coliforms count. E.coli was identified in 2 (6.67%) out of 30 samples analyzed. All the outlets showed unsatisfactory status in hygiene and food preparation. Two of the outlets showed presence of E.coli particularly in the salmon sushi. This indicates that the microbiological quality of sushi sold in the food outlets are far from satisfactory and their safety is doubtful.